2015
DOI: 10.1007/s10198-015-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct medical costs attributable to type 2 diabetes mellitus: a population-based study in Catalonia, Spain

Abstract: We estimated healthcare costs associated with patients with type 2 diabetes compared with non-diabetic subjects in a population-based primary care database through a retrospective analysis of economic impact during 2011, including 126,811 patients with type 2 diabetes in Catalonia, Spain. Total annual costs included primary care visits, hospitalizations, referrals, diagnostic tests, self-monitoring test strips, medication, and dialysis. For each patient, one control matched for age, gender and managing physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 31 publications
5
96
0
14
Order By: Relevance
“…A number of studies has demonstrated the high societal and medical costs of DM from a community perspective . However, there exist few studies that have specifically quantified hospital costs in patients with and without diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies has demonstrated the high societal and medical costs of DM from a community perspective . However, there exist few studies that have specifically quantified hospital costs in patients with and without diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Previous German and international studies have shown that diabetes is associated with a higher usage of medical services and incapacity to work, 5 6 resulting in significantly higher direct and indirect societal costs. [7][8][9][10][11][12][13][14][15][16] For example, a study based on administrative health claims data (AOK/KV Hesse) showed that the excess direct medical costs of diabetes mellitus in 2009 averaged €21 billion in Germany. 17 Studies from the USA and England reported annual direct medical costs of $176 billion and £10 billion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, diabetes-related costs accounted for 8% of all healthcare system expenditures, with EUR 5.1 billion in direct costs and EUR 2.8 billion in lost labor productivity [6]. A study in the Catalonia region estimated that, in 2011, annual direct medical costs for a patient with type 2 diabetes were EUR 3110, compared with EUR 1803 for a patient without diabetes [7]. Extrapolating these results to all of Spain and assuming a prevalence of 7.8%, the authors estimated yearly direct costs of type 2 diabetes to be around EUR 10 billion.…”
Section: Introductionmentioning
confidence: 99%